Unraveling Whole-Genome Sequence and Functional Characterization of P. megaterium PH3 - Xiaohan Zhang; Junbo Liang; Dong Zhang; Liang Wang; Shuhong Ye (Foods)
Priestia megaterium (P. megaterium PH3) is an endophytic bacterium isolated from peanuts. It has natural resveratrol production ability and shows potential application value. This study analyzed its genetic function and metabolic mechanism through whole-genome sequencing and found that the genome size is 5,960,365 bp, the GC content is 37.62%, and 6132 genes are annotated. Functional analysis showed that this strain contained 149 carbohydrate active enzyme genes, 7 secondary metabolite synthesis gene clusters, 509 virulence genes, and 273 drug-resistance genes. At the same time, this strain has the ability to regulate salt stress, low temperature, and hypoxia. Genomic analysis reveals a stilbene-synthase-containing type III polyketide synthase gene cluster that contributes to resveratrol synthesis. A safety assessment showed that the strain is non-hemolytic, does not produce amino acid decarboxylase, and is not resistant to multiple antibiotics. In the mouse model, P. megaterium PH3 did not have significant effects on body weight, behavior, or physiological indicators. These results provide important basic data and theoretical support for its industrial application and the research and development of plant protection agents.